Passivization and pseudo-relatives with perception verbs in Spanish - Carranza, Fernando Martín (2023)
Perception verbs in Spanish (e.g. ver, ‘to see’; oír, ‘to hear’) can combine simultaneously with a direct object and different kinds of clausal modifiers. One of these are pseudo-relative clauses (e.g. que se caía,‘that he fell’, in Ana vio a Juan que se caía, literally ‘Ana saw John that he fell’, with the meaning of ‘Ana saw John falling’). If the verb combines with a pseudo-relative, its passivization is no longer possible (*Juan fue visto que se caía, literally John was seen that he fell). In this paper, we contend that this pattern is due to an obviation effect. This explains not only the behavior of these verbs regarding passivization, but also the fact that reflexive and passive se with pseudo-relatives also leads to ungrammatical results. We conjecture that this obviation effect may be related to a defectiveness of the embedded complementizer. We draw a possible analysis for this behavior in terms of an anti-logophoric operator in the periphery of the pseudo-relative.